Accurate numerical modelling the GaAs MESFET current-voltage characteristics - Merabtine, N.; Khemissi, S.; Zaabat, M.; Belgat, M.; Kenzai, C. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2004)
In this paper, we present a computing model of the current-voltage (I-V) characteristics of a gallium arsenide Schottky barrier field effect transistor called GaAs MESFET. This physical model is based on the two-dimensional analysis of the Poisson equation in the active region under the gate. In this frame, we elaborated a simulation software based on analysis of expressions that we have previously set up [1-3], the obtained theoretical results are discussed and compared to the experimental ones.